2022
DOI: 10.3389/fcimb.2022.947954
|View full text |Cite
|
Sign up to set email alerts
|

A scoring system developed from a nomogram to differentiate active pulmonary tuberculosis from inactive pulmonary tuberculosis

Abstract: PurposeThis study aimed to develop and validate a scoring system based on a nomogram of common clinical metrics to discriminate between active pulmonary tuberculosis (APTB) and inactive pulmonary tuberculosis (IPTB).Patients and methodsA total of 1096 patients with pulmonary tuberculosis (PTB) admitted to Wuhan Jinyintan Hospital between January 2017 and December 2019 were included in this study. Of these patients with PTB, 744 were included in the training cohort (70%; 458 patients with APTB, and 286 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…41 In addition, MHR has been indicated to have greater diagnostic significance in conditions such as tuberculosis and osteoarthritis. 42,43 In the prediabetic stage, an increase in monocytes count and pro-inflammatory subtypes has been observed. 18 In a 5-year cohort study, it was found that the dysregulation of circulating immune cells and inflammatory factors was associated with dynamic disruptions in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition, MHR has been indicated to have greater diagnostic significance in conditions such as tuberculosis and osteoarthritis. 42,43 In the prediabetic stage, an increase in monocytes count and pro-inflammatory subtypes has been observed. 18 In a 5-year cohort study, it was found that the dysregulation of circulating immune cells and inflammatory factors was associated with dynamic disruptions in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In TB, previous studies have focused on the diagnostic value of inflammatory markers. For example, high-sensitivity C-reactive protein to lymphocyte ratio (HSCLR) was proven to be an important biomarker for distinguishing active PTB from inactive PTB ( Yu et al., 2022b ). Similarly, CLR can be used to predict the prevalence of T2DM in patients with active PTB ( Yu et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that some laboratory parameters often available in clinical practice (eg C-reactive protein(CRP), hemoglobin(Hb), albumin(Alb), RDW-CV, AGR, etc.) have proven to be valuable in the prediction of TB activity 7 and prognosis 8–12 in previous studies. Additionally, the coagulation function in TB is receiving more and more attention.…”
Section: Introductionmentioning
confidence: 99%